THE EMAIL NEWSLETTER CAMPAIGN DESIGN FOR CV. SUKA TRIP ASIA - Muhammad Fikri Haikal; Aswar; Satriadi (This journal is published by the Vocational School of Universitas Sebelas Maret., 2025)
This research aims to design and address the communication gap between CV. Suka Trip Asia and its potential and current customers through a structured campaign strategy using email newsletters. The approach adopts the 4D development model: define, design/ideate, develop, and disseminate. The results demonstrate that the designed email newsletter campaign meets the company’s needs in delivering appealing offers and solving communication challenges, as proven by increased customer engagement. At the dissemination stage, a positive click rate was achieved, indicating the effectiveness of message delivery and its ability to encourage user actions.